Standardisation of Cross Cut Saws - Grewal, G. S. (Indian Forester, 1986)
Introduction of improved cross cut saws&bow saws can not only reduce the wastage in wood but these can save a lot of effort on the part of worker too. Hence the need for standardisation of saws. The criteria for a good saw should be performance based. It should take into account factors such as cutting efficiency, life of the saws and effort required to cut. The approach should be to demand a specific performance and not a particular teeth pattern etc.